Ocular Manifestations of Systemic Hypertension: Its Management and Prevention - Bhattarai, Sanjeev; Adhikari, Pragati Gautam; Chhetri, Suraj (Nepal Mediciti Medical Journal, 2023)
Hypertension is identified when blood pressure is higher than 140/90 mm of Hg. It is in public health concern in the form of systemic disease as well as in ocular manifestations. The main site for ocular changes in hypertension is retina which shows marked arteriolar attenuation, hemorrhages, oedema and swelling of the optic disc. If further uncontrolled vision threatening conditions like revascularization and even retinal detachment may occur in later stages. Other common ocular manifestations are subconjunctival hemorrhages, strabismus, ptosis and cranial verve palsies. Most of the recent treatment is focused in retinal laser therapy and intravitreal injection of anti VEGFs agents. To prevent the ocular manifestations blood pressure should be in strict control with sodium and salt restriction in diet. Adequate physical exercise and proper nutrition can also play crucial role for its management.